Efektivitas Kolaborasi Guru dan Wali Murid dalam Membagun Motivasi Belajar Bahasa Arab Siswa di Madrasah Ibtidaiyah NW Tanak Beak - Ats-Tsauri , Muhammad Sufyan (Al Banin : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to examine the effectiveness of collaboration between teachers and parents in enhancing students' motivation to learn, particularly in Arabic reading skills at Madrasah Ibtidaiyah (MI), specifically at MI NW Tanak Beak. Through a collaborative approach, it is hoped that appropriate strategies can be found to address students' difficulties in reading Arabic and ultimately improve their academic performance. In this article, Arabic language learning is considered one of the main foundationsfor being able to reHowever, students' interest in learning Arabic at several madrasahs is still low. Guidance in Arabic subjects is not only the responsibility of the school as a formal institution but also involves the family as the smallest unit in society. Collaboration between the school and the family is becoming increasingly important to ensure children receive a comprehensive and balanced education. Through effective cooperation between these two parties, children's potential can develop optimally, both academically, emotionally, and socially.ad the Quran, as Arabic, being the language of the Quran, plays a significant role in Islamic education.